Spatiotemporal ecology and potential displacement of white sharks in southern Africa - Towner, Alison (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
The white shark Carcharodon carcharias (Linnaeus, 1758) is one of the largest predatory sharks, with a cosmopolitan global distribution. The objective of this thesis was to explore the spatiotemporal ecology of this species in coastal South Africa, from both a fine and large-scale perspective (a bay versus the entire coastline). Furthermore, this study aimed to identify and quantify the impacts of a novel biological driver on white shark movement in the region. This study revealed that two hunting modes were employed by white sharks to hunt seals. Mixed Hidden Markov models (HMMs) were applied to acoustic tracking data of 14 white sharks in the aggregation area, to quantify changing movement states (area-restricted searching vs. patrolling) and the factors that influenced them. White sharks demonstrated individual preferences for fine-scale movement patterns, which may be related to their use of different hunting modes. As such, individual variability should be considered when modelling the behavioural effects of predators on prey species. Risk-induced fear effects exerted by top predators are pervasive in terrestrial and marine systems, with lasting impacts on ecosystem structure and function. The loss of top predators can disrupt ecosystems and trigger trophic cascades, but the introduction of novel apex predators to ecosystems is not well understood. In 2017, during the middle of the data collection period of this study, a rare shark-eating morphotype of killer whale Orcinus orca appeared along the Western Cape coast. This highly distinctive pair of killer whales preyed on at least eight white sharks, seven at Gansbaai. Sightings per unit effort and telemetry data revealed that white sharks emigrated from the site, following these attacks, in response to further sightings of the killer whales. White sharks responded rapidly to risk from a novel predator, and their absence triggered the emergence of another meso-predator, the bronze whaler shark Carcharhinus brachyurus, demonstrating trophic changes in mesopredator composition at the site, determined by sightings data from shark dive operators. Unique aerial footage was analysed on the same killer whales hunting white sharks at another aggregations site, 300 km east, Mossel Bay. This footage substantiated the hypothesis that killer whales are hunting white sharks in South Africa and it revealed the hunting behaviour of the killer whales in additional to the evasive strategies utilised by the white sharks. Cage diving vessel and drone survey data confirmed that white sharks exhibited flight responses for at least 45 days from Mossel Bay and were similar to the behavioural patterns observed in Gansbaai. Furthermore, cultural transmission was documented, with other adult killer whales hunting white sharks in Mossel Bay, together with the known pair. Large-scale movement data from 118 individual white sharks fitted with with V16 R-coded acoustic tags between 2012 and 2022 were examined. Spatial network analysis was applied to note if any differences occurred in coastal space use between white sharks pre- and post-killer whale presence. Declines in white shark acoustic detections were noted after 2018, along the coast, and the complete disappearance of detections in the Western Cape hotspots of False Bay (Cape Town) and Gansbaai between 2015 and 2018. There are broader ecological, economic, and bather safety impacts of white sharks being displaced by killer whales in South Africa, and while there are no clear solutions, suggestions for management are proposed as these interactions are likely to continue.
Keywords: Predation (Biology); Ecology -- Africa, Southern; Displacement activity (Animal behavior); Biotelemetry; White shark -- Geographical distribution